2019
DOI: 10.1590/2177-6709.24.1.062-067.oar
|View full text |Cite
|
Sign up to set email alerts
|

Do laypersons perceive aesthetic differences between coated and uncoated orthodontic archwires?

Abstract: Introduction: Aesthetic brackets are routinely combined with metallic wires in fixed orthodontic therapy, mainly due to the disadvantages of the clinical use of aesthetic archwires. The current situation needs to be explored in the literature by considering laypersons’ perceptions. Objective: The objective of this cross-sectional study was to evaluate laypersons’ aesthetic perceptions of metal archwires with and without aesthetic coating. Three age ranges and both sexes were evaluated. Methods: A volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…For being considered esthetic, this result was expected, compared to the conventional metallic wires. Pinzan-Vercelino et al 21 found in their study that the epoxy resin wire was the most attractive. However, in their study, the wires were evaluated only for 30 seconds each.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…For being considered esthetic, this result was expected, compared to the conventional metallic wires. Pinzan-Vercelino et al 21 found in their study that the epoxy resin wire was the most attractive. However, in their study, the wires were evaluated only for 30 seconds each.…”
Section: Discussionmentioning
confidence: 96%
“…In order to reduce the interference in the evaluators perception, monocrystalline ceramic accessories and silicone esthetic ligatures were used, since these materials were the most esthetic of their categories. 8 , 21 Besides, a patient with a great occlusion and smile esthetics, good teeth alignment and leveling and normal overbite and overjet was selected for orthodontic appliance bonding, in order to not interfere in the evaluation of the wire esthetics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations